The death and life of Zebulon Finch. Volume one, At the edge of empire - Kraus, Daniel, 1975- (Simon & Schuster BFYR, 2015)
"The story follows Zebulon Finch, a teenager murdered in 1896 Chicago who inexplicably returns from the dead and searches for redemption through the ages"--